Origen, Domesticación y Distribución de Opuntia ficus-indica - Kiesling, Roberto (Journal of the Professional Association for Cactus Development, 1998)
Based on historic reports, cytological evidence, bibliographic references, and taxonomic evidence from herbarium specimens and in the field, this paper concludes that the common prickly-pear plant, Opuntia, a horticultural plant whose domestication began 9000 years ago by the ancient Mexicans, has been divided erroneously into various species. During domestication from the wild species (2X), O. ficus-indica species acquired a higher ploidy (6X and 8X) level through natural hybridization. The present wild plants of Mexico have been described as O. streptacantha and O. megacantha. After the discovery of America, O. ficus-indica was introduced into Spain and, later, throughout the Mediterranean basin by sailors who used it as a vegetable to prevent scurvy. In the new locations, new spined and spineless specimens developed from seedlings that exhibited relic traits of the old-world parents. In the new countries, botanists described the "new"specimens as new species. This evidence suggests that the spined and nonspined specimens are only forms of O. ficus-indica, and thus, for nomenclatural reasons, the name O. ficus-indica f. amyclaea (Tenore) Schelle must be used for the spined plants.